giải pt :
a, \(\left(2x-6\right)\sqrt{x+4}-\left(x-5\right)\sqrt{2x+3}=3\left(x-1\right)\)
b, \(\left(4x+1\right)\sqrt{x+2}-\left(4x-1\right)\sqrt{x-2}=21\)
c, \(\left(4x+2\right)\sqrt{x+1}-\left(4x-2\right)\sqrt{x-1}=9\)
d, \(\left(2x-4\right)\sqrt{3x-2}+\sqrt{x+3}=5x-7+\sqrt{3x^2+7x-6}\)
<=> \(\left(x^2+1\right)+3x-x\sqrt{x^2+1}-3\sqrt{x^2+1}=0\)
<=> \(\left(\left(x^2+1\right)-3\sqrt{x^2+1}\right)+\left(3x-x\sqrt{x^2+1}\right)=0\)
<=> \(\sqrt{x^2+1}\left(\sqrt{x^2+1}-3\right)+x\left(3-\sqrt{x^2+1}\right)=0\)
<=> \(\left(\sqrt{x^2+1}-3\right)\left(\sqrt{x^2+1}-x\right)=0\)
<=> \(\sqrt{x^2+1}-3=0\) hoặc \(\sqrt{x^2+1}-x=0\)
+) \(\sqrt{x^2+1}-3=0\) => x2 + 1 = 9 <=> x2 = 8 <=> \(x=2\sqrt{2}\) hoặc \(x=-2\sqrt{2}\)
+) \(\sqrt{x^2+1}-x=0\)<=> \(x^2+1=x^2\) và x > 0 <=> 1 = 0 (Vô lí)
Vậy....
hâm mộ có ngĩa là lấy chảo đến mộ mà hâm